Oxidative stress and galectin-3 levels during skin grafting after hand injury: gender differences: Oxidative stress, galectin-3 and skin grafting - Andric, Kristina; Jakovljevic, Vladimir; Zivkovic, Vladimir; Veselinovic, Mirjana; Bolevicg, Sergey; Petrovich Fisenko, Vladimir; Joksimovic Jovic, Jovana; Andjic, Marijana; Lazarevic, Nevena; Andric, Nikola; Dimkic Milenkovic, Andjela; Vulovic, Dejan (Cellular and Molecular Biology, 2024)
The study included 40 patients of both genders who underwent skin transplantation after a hand injury. The study aims to evaluate the oxidative stress parameters in patients’ blood and serum levels of galectin-3 in order to investigate gender differences pre- and post- skin transplantation. The results of the study suggest a significant increase in superoxide anion radical levels, catalase activity, and reduced glutathione levels in females before skin transplantation. The surgical treatment caused significant increase in superoxide anion radical and hydrogen peroxide levels as prooxidants in males, while superoxide dismutase and catalase activity were also increased 7 days after the procedure. In females, superoxide anion radical and TBARS levels increased after surgical procedure as well as the activity of catalase. Regarding galectin-3 levels, a significant interaction between gender and time was observed (gender×time; p=0.000). Correlation analysis of different oxidative stress markers with gal-3 revealed the existence of a significant negative correlation of superoxide anion radical, catalase, and reduced glutathione with gal-3, but only in female patients. It can be concluded that OS as well as galectin-3 play important roles at least in the first 7 days of the postoperative period.